The Strategy of General Election Commission (KPU) in Increasing Women's Roles in Pesawaran District - Farida, Ida; Ardiansyah, M; Reffiani, Yetti (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The election is the embodiment of democracy in Indonesia, the political participation of the people in elections which is implemented in the form of voting rights by people who already have the right to vote. Article 1 paragraph 2 of the 1945 Constitution of the Republic of Indonesia states that sovereignty is in the hands of the people and is exercised according to the Constitution, in its implementation, an Election is held as a process of channelling the aspirations of the people who already have rights where all citizens have the same rights to choose and be chosen to be a leader. The purpose of this research is to provide an understanding and description of the strategy of the General Election Commission in enhancing the role of women in the Regional Head Elections in the Pesawaran District in 2020. This research uses qualitative data analysis methods, namely describing and analyzing the data and data sources obtained and then described in the form of real explanation. The results showed that the strategy of the General Election Commission (KPU) of Pesawaran Regency in increasing the role of women in regional head elections was carried out by maximizing the ability of electronic media and internet media to socialize, increasing cooperation from related organizations to socialize, and Validating Voter Data.Keywords: Strategy; General Election Commission (KPU); Role of Women; Regional Head Election; Pesawaran District Strategi Komisi Pemilihan Umum (KPU) Dalam Meningkatkan Peran Perempuan Di Kabupaten Pesawaran AbstrakPemilu merupakan perwujudan dari Demokrasi di Indonesia, Partisipasi politik masyarakat dalam Pemilu yang diimplementasikan dalam bentuk pemberian hak suara oleh masyarakat yang telah memiliki hak untuk memberikan suaranya. Pasal 1 ayat 2 Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 menyatakan bahwa kedaulatan berada ditangan rakyat dan dilaksanakan menurut Undang-Undang Dasar, dalam pelaksanaannya maka diadakan Pemilu sebagai proses penyaluran aspirasi rakyat yang telah memiliki hak dimana seluruh warga negara memiliki hak yang sama untuk memilih dan dipilih menjadi pemimpin. Adapun tujuan penelitian ini adalah untuk memberikan pemahaman dan gambaran mengenai strategi Komisi Pemilihan Umum dalam peningkatkan peran perempuan pada Pemilihan Kepala Daerah di Kabupaten Pesawaran Tahun 2020. Penelitian ini menggunakan metode analisis data kualitatif yaitu mendeskripsikan serta menganalisis data dan sumber data yang diperoleh kemudian dijabarkan dalam bentuk penjelasan yang sebenarnya. Hasil penelitian menunjukkan bahwa strategi Komisi Pemilihan Umum (KPU) Kabupaten Pesawaran dalam meningkatkan peran perempuan pada pemilihan kepala daerah dilakukan dengan memaksimalkan kemampuan media elektronik dan media internet untuk bersosialisasi, meningkatkan kerjasama dari organisasi-organisasi terkait untuk bersosialisasi, dan Validasi Data Pemilih.Kata Kunci: Strategi; Komisi Pemilihan Umum (KPU); Peran Perempuan; Pemilihan Kepala Dearah; Kabupaten Pesawaran Стратегия Всеобщей избирательной комиссии (KPU) по повышению роли женщин в округе Песаваран АннотацияВыборы - это воплощение демократии в Индонезии. Политическое участие людей в выборах осуществляется в форме избирательных прав людей, которые уже имеют право голоса. Пункт 2 статьи 1 Конституции Республики Индонезия 1945 года заявляет, что суверенитет находится в руках народа и осуществляется в соответствии с Конституцией. При его осуществлении выборы проводятся как процесс отражения устремлений людей, которые уже имеют права. Все граждане имеют одинаковое право голосовать и быть избранными в качестве лидеров. Цель этого исследования - дать понимание и описание стратегии Всеобщей избирательной комиссии по повышению роли женщин на выборах главы региона в округе Песаваран в 2020 году. В этом исследовании используются методы качественного анализа данных, а именно описание и анализ данных. Источник полученных данных затем описывается в форме реального объяснения. Результаты показали, что стратегия Всеобщей избирательной комиссии (KPU) Округа Песаваран по повышению роли женщин на выборах глав региона была реализована за счет максимального увеличения возможностей электронных и интернет-СМИ к общению, расширения сотрудничества со стороны связанных организаций для общения и проверки данных избирателей.Ключевые Слова: Стратегия; Всеобщая избирательная комиссия (KPU); роль женщин; выборы главы региона; Округ Песаваран